262 Obesity-related neutrophilia in endometrial cancer. (18th September 2019) - Cheung, M; O'Brien, O; Byrne, D; Geoghegan, T; LeRoux, C; Brennan, D
Abstract : Objectives: Obesity and metabolic syndrome are significant risk factors for endometrial cancer (EC). This case-control study aimed to assess the relationship between visceral fat and systemic inflammatory markers in EC and cervical cancer (CC). Methods: ImageJ software was used to measure the visceral fat percentage (VFP) on a L3/4 CT slice, for 22 EC, 20 CC. Pre-treatment full blood counts were used to assess inflammatory ratios. Results: Mean BMI (32.56 vs 25.87 kg/m 2, p=0.03) and VFP (33.4 vs 24.0%, p=0.0018) was higher in EC compared to CC patients. BMI did not correlate with VFP. Mean pre-operative leukocytes (8.5 vs 7, p=0.044) and neutrophils (5.85 vs 4.32, p=0.019) were higher in EC patients. There was no difference in the lymphocyte-neutrophil-ratio or lymphocyte-monocyte-ratio, however the neutrophil-monocyte-ratio (NMR) was higher in the EC group (11.27 vs 8.28, p=0.018). This was due to the significant neutrophilia in the EC group (68.9% vs 60.5%, p=0.037) as there was no difference in monocytes in either group. No inflammatory ratio correlated with VFP. Conclusions: VFP and BMI do not correlate, and no white cell ratio correlated with either value in this study. Obesity related neutrophilia may be an important target in EC that warrants further investigation